Studi Kelaikan Tower BTS Berdasarkan Sudut Kemiringan, Kekencangan Baut, Kekuatan Beton Serta Pengukuran Ground - Vicky Prasetia; Arif Sumardiono; Sugeng Dwi Riyanto; Muhamad Yusuf (P3M Politeknik Negeri Cilacap, 2024)
Telecommunication Network Tower is a tower made of a series of iron profiles or rectangular or rectangular pipes, or rectangular long pipes intended to accommodate antennas and radio transmitters and receivers of telecommunications and information waves. In principle, BTS towers have the function of connecting network user communication devices to other networks. To support the smooth operation of the network, the building will remain solid and secure for a certain period. Investigation of the feasibility condition of the tower structure is very important to determine the overall condition of the tower structure. The methods used are hammer test, check bolt tightness (torque), measure slope (vertical), grounding, and visual observation. From the results of the test data obtained the average bolt tightness is 432.86 Nm. The tower slope test of 1.90 cm on leg A smaller than 3.6 cm is considered good because it is still within the tolerance limit of the bat slope, the average soil resistance measure smaller than1 ohm used is very good, and the visual physical conditions are very similar, so it can be done Tower in safe and working condition